PAW18 Blood markers and the diagnosis of stroke or transient ischaemic attack in the emergency department: a prospective cohort study. Issue 11 (22nd October 2010) - Whiteley, W; Lowe, G D; Rumley, N; Wardlaw, J M; Green, V; Welsh, P; Dennis, M S; Sandercock, P A G
Abstract : Background: Biomarkers of a number of pathophysiological processes might improve the clinical diagnosis of stroke and transient ischaemic attack (TIA). Methods: We recruited symptomatic patients with suspected stroke or TIA <24 h after onset. We measured markers of inflammation, thrombosis; thrombolysis, cardiac dysfunction and cerebral damage. A panel of stroke physicians, neurologists and neuro-radiologists reviewed the clinical features, brain imaging and subsequent course of each patient to make the gold standard diagnosis. We constructed multivariate logistic models to analyse the data. Results: We recruited 405 patients with suspected stroke (285 stroke or TIA, 180 mimics) at a median of 7 h (IQR 3–19 h) after symptom onset. Higher levels of Ln NT pro-BNP (OR 2.2 (95% CI 1.5 to 3.0) 75th to 25th centile) and t-PA (OR 1.6 (1.2 to 2.2)) were associated with a diagnosis of TIA or stroke. Adjustment for neurological impairment and age attenuated these associations. The associations of higher levels of adiponectin (OR 1.8 (1.2 to 2.4)) and IL-10 (OR 1.1 (1.0 to 1.1)) with a diagnosis of mimic were robust to adjustment for neurological impairment, age and infection. A model with eight markers from systematic review had no better diagnostic performance than an emergency department clinician. Conclusion: We found no single marker or combination of markers that positively predicted a diagnosis of stroke or TIA independently of neurological impairment and age, or added usefully to the clinical diagnosis.